Investigating the nature of the ultraluminous X-ray sources in the galaxy NGC 925. Issue 2 (3rd March 2022) - Salvaggio, Chiara; Wolter, A; Pintore, F; Pinto, C; Ambrosi, E; Israel, G L; Marino, A; Salvaterra, R; Zampieri, L; Belfiore, A
Abstract: Variability is a powerful tool to investigate properties of X-ray binaries (XRB), in particular for Ultraluminous X-ray sources (ULXs) that are mainly detected in the X-ray band. For most ULXs the nature of the accretor is unknown, although a few ULXs have been confirmed to be accreting at super-Eddington rates on to a neutron star (NS). Monitoring these sources is particularly useful both to detect transients and to derive periodicities, linked to orbital and super-orbital modulations. Here, we present the results of our monitoring campaign of the galaxy NGC 925, performed with the Neil Gehrels Swift Observatory . We also include archival and literature data obtained with Chandra, XMM–Newton, and NuSTAR . We have studied spectra, light curves, and variability properties on days to months time-scales. All the three ULXs detected in this galaxy show flux variability. ULX-1 is one of the most luminous ULXs known, since only 10 per cent of the ULXs exceed a luminosity of ∼5 × 10 40 erg s −1, but despite its high flux variability we found only weak spectral variability. We classify it as in a hard ultraluminous regime of super-Eddington accretion. ULX-2 and ULX-3 are less luminous but also variable in flux and possibly also in spectral shape. We classify them as in between the hard and the soft ultraluminous regimes. ULX-3 is a transient source: by applying a Lomb–Scargle algorithm, we derive a periodicity of ∼126 d, which could be associated with an orbital or superorbital origin.